About Literacies and Competences in the Digital Age: Case Study - Castaño Muñoz, Wilson (2014)
There is a lot of information about what digital skills people should have to communicate successfully on the internet. The literature on the subject refers to a range of disciplinary fields that analyze the different meanings and variables of the term "Literacy" (Bawden, 2002), although these notions are more related to library and information science. This article outlines some concepts and terms that are intended to describe the competences and skills in information management that a person must have to be considered information literate. Finally, this paper presents the results of a research made on researchers at the Institute of Political Studies of the University of Antioquia (IPS), Medellin, Colombia. Some of their skills and literacies are analyzed, related to how they search and retrieve information and the level of knowledge researchers need to have to function in an environment that has changed substantially from the traditional paper format, which they were fully used to, to an increasing prevalence of electronic and digital media.